Antroposceniczność. Krajobraz jako nowa opowieść klimatyczna - Stańczyk, Marta (Przestrzenie Teorii, 2025)
The article Anthroposcenicity. Landscape as a New Climate Narrative examines the challenges of representing climate disasters and the Anthropocene in visual culture. Using the case of the 2024 floods in Poland as a starting point, it highlights the limitations of traditional media in capturing the scale and processual nature of environmental crises. The author explores how cinema moves away from the narratives of Hollywood disaster films – which often reinforce anthropocentric perspectives – and presents alternative approaches that allow for the dehierarchization of the human viewpoint. Drawing on the concepts of Andrzej Marzec, Timothy Morton, and David Matless, the article introduces the term anthroposcenicity as a framework for rethinking film aesthetics in the Anthropocene. By analyzing films that expand spatial and temporal scales, the text emphasizes the potential of cinema to shift narratives from an anthropocentric perspective to ecological and posthumanist storytelling.